ENHANCING OF STUDENTS LEARNING OUTCOMES USED PROBLEM BASED LEARNING (PBL) ON REFRIGERATION SYSTEMS AND INSTALLATIONS - Oktapiana, Romy; Kusuma, Inu Hardi; Berman, Ega Taqwali (Journal of Mechanical Engineering Education, 2020)
The purpose of this study is to obtain data on student learning outcomes improvement using problem based learning (PBL) models on refrigeration systems and installations. This research was conducted at SMKN 1 Cimahi class XII TPB on the Refrigeration and Air Conditioning Engineering Expertise Program. The research sample of 29 students. The PBL model is implemented in three learning cycles that refer to the Classroom Action Research method. The observations of the three learning cycles that have been carried out give a picture of changes in student learning outcomes. The increase in learning outcomes can be seen from the average value of N-Gain in each cycle. N-Gain values obtained in cycle I, up to cycle III were 0.41, 0.52 and 0.59, respectively. The increase in N-Gain value from cycle I to cycle II was 27% and the increase in N-Gain value from cycle II to cycle III was 13%. All N-Gain values obtained are in the medium criteria. This research has implications for student learning activities that are more directed and planned so that students have activities at each stage of problem solving given by the teacher.